PENGARUH STRES DAN DISIPLIN KERJA KARYAWAN TERHADAP KEPUASAN DAN KINERJA KARYAWAN PT. BANK PERKREDITAN RAKYAT (BPR) MITRATHAMA ARTHABUANA DI KABUPATEN BANJAR - Mahriani, Elida (Islamic Economics and Business Faculty of UIN Antasari, 2018)
Employee Performance can be measured by their compliance with company policy, the ability to complete the jobs, the timing of completing the work, the quality of results. On the other hand, a too tight work can affect the psychological state of the employees, which may also then affect their performance. The study is conducted in BPR Mitrathama Arthabuana of Kabupaten Banjar, to answer the formulation below: (1) Do stress and work discipline partially affect on job satisfaction of employees?; (2) Do stress and work discipline partially affect on Employee Performance?, and (3) Does Satisfaction affect the performance of employees? This study uses Quantitative Methods, the data is taken via questionnaires, and then analyzed using Partial Least Square (PLS) model with t-test via smartPLS software version 2.0.M3. The result of the research: (1) The t-statistic value of the path of the influence of Stress on Satisfaction is 9,464 and to Satisfaction and Performance is 2,617 bigger than t-table of the normal distribution (1,96), meaning significant, hypothesis 1 accepted. (2) The t-statistic value of Discipline effect on Satisfaction is 3,190 and to Satisfaction and Performance is 2,617 bigger than t-normal distribution table (1,96), meaning significant, hypothesis 2 accepted. (3) The t-statistic value of the influence of Satisfaction on Performance is 2,617 is greater than the normal t-distribution table (1,96), meaning significant, hypothesis 3 is accepted.